Compliance costs of transfer pricing in case of SMEs: Czech case - Veronika Solilová; Danuše Nerudová; Hana Bohušová; Patrik Svoboda (European Financial and Accounting Journal, 2017)
Small and medium sized enterprises account for over 99% of all companies in Eu-ropean Union and have very important position in the EU economy in the area of growth and employment. However, they face great deal of obstacles, such as com-pliance costs of taxation, 28 different tax systems in Europe, difficult transfer pric-ing rules and so on. Further, compliance costs of taxation are regressive with regard to firm size and significantly higher in case of enterprises with foreign branch or subsidiary in comparison with enterprises which are not internationalized. Moreo-ver, compliance costs are increasing through strict and difficult transfer pricing rules among European countries. Therefore, taxes and new obligations should be carefully designed so that they can address the disproportionately high tax compli-ance burdens faced by those enterprises. Unfortunately, there does not exist a study determining compliance costs of transfer pricing issue in the literature. Therefore, the aim of paper is to determine compliance costs of transfer pricing issues in case of SMEs. The results are based on the questionnaire distributed among Czech parent companies having subsidiaries in Europe and Czech subsidiaries having a parent company in Europe. Based on the results we can conclude that costs for managing of transfer pricing requirements can reach from EUR 6,430 to 7,704 per year, time needed for this issue between 27 and 35 working days and in case of comparison with corporate tax collection it represents between 3.90 % and 12.74 %.
Keywords: F23; G38; H26; M1; 650; Compliance costs; Small and medium sized enterprises; Transfer pricing rules